Pengaruh Pemberian Kombinasi Jus Belimbing Manis (Averrhoa carambola) dan Labu Siam (Sechium edule) terhadap Pemeliharaan Tekanan Darah: The Effect of Combination of Starfruit (Averrhoa carambola) and Chayote (Sechium edule) Juice on Blood Pressure Maintenance - Nugrahiwulan Oktaviani; Riski Sulistiarini; Vita Olivia Siregar (Proceeding of Mulawarman Pharmaceuticals Conferences, 2021)
Starfruit (Averrhoa carambola) and chayote (Sechium edule) contain potassium which can balance blood pressure. This study aims to determine the characteristics of the respondents including gender, age, education, occupation, physical activity, and regular exercise, to determine the blood pressure profile of the respondents, and to determine the effect of giving a combination of starfruit juice and chayote in the Samarinda Ulu District. The method used is a quasi-experimental method by measuring pre and post treatment for 5 days. Data collected on the characteristics of respondents obtained the highest percentage of women 95%, ages 18-30 years 95%, high school education 95%, college student job 95%, low physical activity 95%, and not doing regular exercise 70% . The respondent's blood pressure profile for 14 days every 3 days shows the Mean Artery Pressure value in the normal and high normal categories. The results of the combination of starfruit juice and chayote can maintain blood pressure, with a mean decrease in systolic and diastolic 12.2 ± 7.97 mmHg and 6.5 ± 3.60 mmHg for the treatment group. Based on the results, it can be concluded that the combination of sweet star fruit juice and chayote can maintain blood pressure in normotensive respondents.